Optimization Policies for Inventory Model with Deterministic Demand Based on Selling Price and Promotional Efforts Under Inflationary Conditions - Rupali Jindal; Arun Krushna Padhihari; Leena Prasher (PT FORMOSA CENDEKIA GLOBAL, 2022)
This paper constructs an economic order quantity model considering demand dependent upon selling price, time and promotional eorts made by the firm/sales team. Items ar deteriorating with a constant rate.The cost for holding the items is taken as constant. Cost of advertisement is assumed to be quadratic function of marketing eorts. The objective of the paper is to determine economic replenishment quantity in inationary conditions so as to maximize prot. Numerical example is presented to illustrate the theory. Graphical presentation is made to describe the optimality of the model with suitable sensitivity analysis